Using Random Ordering in User Experience Testing to Predict Final User Satisfaction - Kitti Koonsanit; Daiki Hiruma; Vibol Yem; Nobuyuki Nishiuchi (Informatics, 2022)
In user experience evaluation (UXE), it is generally accepted that the order in which users perform tasks when using a product is often random rather than fixed. UXE based on these so-called randomly ordered tasks is challenging. Although several articles have been published on UXE, none have proposed a technique to evaluate the significance of randomly ordered tasks. In this study, we propose a new approach to predict final user satisfaction based on UX related to randomly ordered tasks. We aimed to study the importance of task order in the UX. In the main experiment, 60 participants completed questionnaires about satisfaction while performing a series of tasks on a travel agency website. Among the machine learning models tested, we found that accounting for the order or sequence of actions actually performed by users in a support vector machine (SVM) algorithm with a polynomial kernel produced the most accurate predictions of final user satisfaction (97%). These findings indicate that some machine learning techniques can comprehend participants’ randomly ordered UX data. Moreover, using random ordering, which accounts for the actual order of actions performed by users, can significantly impact the prediction of final user satisfaction.